Case Report and Supporting Documentation: Acute Kidney Injury Manifested as Oliguria Is Reduced by Intravenous Magnesium Before Cisplatin - Money, Mary Elizabeth; Hamroun, Aghiles; Shu, Yan; Matthews, Carolyn; Ahmed Eltayeb, Sara; Ciarimboli, Giuliano; Metz, Christine Noel (Frontiers in Oncology, 2021)
After more than four decades of post-approval, cisplatin is still an important treatment for numerous cancers. However, acute kidney injury (AKI), defined as significant impairment of renal filtration as discussed below, is the major limiting side effect of cisplatin, occurring in approximately 30% of patients (25–33% after the first course). Cisplatin also damages the kidneys’ ability to reabsorb magnesium in 40–100% of patients, with collateral health risks due to subsequent hypomagnesemia. Multiple methods and drugs have been proposed for preventing cisplatin-induced AKI, including saline infusion with or without mannitol, which has not always prevented AKI and has been found to activate a cellular stress response in renal tubular cells. While numerous reports and trials, as well as the National Comprehensive Cancer Network (NCCN), support premedication with magnesium and hydration, this practice has not been universally accepted. Many clinics administer intravenous magnesium (IV) only after identification of hypomagnesemia post-cisplatin treatment, thus placing patients at risk for AKI and chronic renal loss of magnesium. We present the following case report and additional supporting evidence identifying the immediate effect of IV magnesium prior to intraperitoneal cisplatin for cycle 4 because of documented hypomagnesemia resulting in normalization of oliguria, which had been experienced for the first three cycles. The patient subsequently requested and received IV magnesium before cisplatin for the next two cycles with continuation of normal urinary output. The effect of pretreatment with IV magnesium on urine output following cisplatin has not been previously reported and further supports pre-cisplatin administration. In addition, two recent meta-analyses of clinical trials and pre-clinical research are reviewed that demonstrate effectiveness of magnesium pretreatment to preventing AKI without reducing its chemotherapeutic efficacy. This case report with additional evidence supports the adoption of administration of 1–3 g IV magnesium before cisplatin as best practice to prevent cisplatin induced AKI and hypomagnesemia regardless of patient baseline serum magnesium levels.